Desain Kapal Pembangkit Listrik Menggunakan Tenaga Gelombang Air Laut Untuk Daerah Papua - Bimo Taufan Devara; Wasis Dwi Aryawan; Ahmad Nasirudin (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2017)
Electricity condition in Indonesia as a whole is still spread not evenly, even for the region of Central and Eastern part of Indonesia, the electricity supply is still far from sufficient. This condition is caused by several reason, and one it is the uneven development in the areas of central and eastern Indonesia. Papua is a province that has lowest level of electrivity in Indonesia, as a whole area only have 47% electricity. In this Final Project will be designed Power Plant Ship as an support unit in Serui City, with the generated power is 36 MWh. The ideal electrical needs of the Serui City approximatedly 8.4 MW, while power is 5.6 MW have been installed so that the power shortage is 2,8 MW. Power Plant Ship design begins with the selection item for producing electricity, such as floats, inverter and battery. Needed two ships for fulfilling the power shortage with each ships used 18 battery with each power of 2 MW and 20 floats with each power of 0.2 MW. After that initial layout was made to find the size of the initial main dimension. Main dimension of the vessel is L = 95.89 m, B = 18.5 m, H = 5.2 m, T = 3.75 m. From this main dimension can be calculated technical calculations and made Lines Plan, General Arrangement and 3D Modeling Design.